2019
DOI: 10.1186/s13068-019-1588-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sugarcane culm and leaf biomass composition and saccharification efficiency

Abstract: Background Lignocellulosic biomass is recognized as a promising renewable feedstock for the production of biofuels. However, current methods for converting biomass into fermentable sugars are considered too expensive and inefficient due to the recalcitrance of the secondary cell wall. Biomass composition can be modified to create varieties that are efficiently broken down to release cell wall sugars. This study focused on identifying the key biomass components influencing plant cell wall recalc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 88 publications
(110 reference statements)
1
13
3
Order By: Relevance
“…In contrast with previous studies [20,33], no clear correlation was observed between glucan (cellulose + MLG) content and glucose release. This may be due to the positive correlation between cellulose and lignin content in these samples.…”
Section: Enzymatic Saccharificationcontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast with previous studies [20,33], no clear correlation was observed between glucan (cellulose + MLG) content and glucose release. This may be due to the positive correlation between cellulose and lignin content in these samples.…”
Section: Enzymatic Saccharificationcontrasting
confidence: 99%
“…The aforementioned study referenced the low lignin levels in immature internodes as a core factor in the observed high digestibility. The tendency for higher digestibility in all internodes vs. leaf tissues contradicts a previous study in sugarcane that displayed the opposite trend, albeit in whole internode and whole leaf comparison [20].…”
Section: Enzymatic Saccharificationcontrasting
confidence: 99%
“…Leaves were also expected to be more present in the finest fractions [ 63 ]. In Poaceae, compared to the stem, leaves are characterized by less xylose and more protein, like in sorghum [ 68 ], more ash [ 69 , 70 ], a lower S/G ratio, like in sugarcane, and less ester-linked p -coumaric [ 70 ]. More leaves in the fine fraction can be assumed from lower xylose or higher protein amounts.…”
Section: Resultsmentioning
confidence: 99%
“…Leaves were also expected to be more present in the nest fractions [45]. In Poaceae, compared to the stem, leaves are characterized by less xylose and more protein, like in sorghum [50], more ash [51,52], a lower S/G ratio, like in sugarcane, and less ester-linked p-coumaric [52]. More leaves in the ne fraction can be assumed from lower xylose or higher protein amounts.…”
Section: Exploring Variability Of Maize Shoot Powdermentioning
confidence: 99%